Pengembangan Learning Space Sebagai Third Teacher Melalui Manajemen Sarana dan Prasarana di SMAN 1 Gambiran - Muhammad Salman Alfarisi; Nurkafidz Nizam Fahmi (CV Edu Tech Jaya, 2026)
The rapid development of technology and the demands of 21st-The rapid development of technology and the demands of 21st-century education require schools to create learning environments that support active, collaborative, creative, and student-centered learning. This study aims to describe the management of educational facilities and infrastructure, analyze the development of learning spaces as a Third Teacher, and examine their contribution to the transformation of learning quality at SMAN 1 Gambiran. This research employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving the principal, vice principal for facilities and infrastructure, teachers, educational staff, and students. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the management of facilities and infrastructure is implemented systematically through planning, procurement, utilization, and maintenance processes. The development of learning spaces is realized through the effective use of classrooms, libraries, computer laboratories, podcast rooms, and various school environments as learning resources. These learning spaces function as a Third Teacher by providing learning stimuli, enhancing students’ comfort, encouraging social interaction, and fostering creativity and independent learning. Furthermore, learning spaces contribute significantly to the transformation of learning quality, as reflected in increased student participation, collaboration skills, learning motivation, and the shift of teachers’ roles from knowledge transmitters to learning facilitators. The study concludes that pedagogically oriented facilities and infrastructure management can serve as a strategic approach to improving learning quality in secondary education.